2013
DOI: 10.1016/j.resp.2012.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Compartmental chest wall volume changes during volitional hyperpnoea with constant tidal volume in healthy individuals

Abstract: Prolonged high-intensity ventilation is associated with the development of rapid shallow breathing with decreased end-inspiratory volumes of all chest wall compartments. During respiratory muscle endurance training using normocapnic hyperpnoea, tidal volume (V(T)) is normally kept constant. The aim of this study was to investigate possible changes in muscle recruitment during constant-V(T) hyperpnoea, to assess potential mechanisms related to rapid shallow breathing. Ten healthy subjects performed 1h of normoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…On the other hand, the increase in ⌬V ab /T E mainly occurred from a decrease in T E throughout application of the protocol, in addition to a higher amount of volume displaced by the compartment. In contrast to diaphragm and expiratory muscles, the inspiratory muscles of the rib cage develop more passive tension for active force development when stretched beyond their optimal size, 40 and perhaps this is why a greater shortening velocity was seen in ⌬V rcp /T I in relation to the other indexes. In general, the increase in shortening velocity could be explained by the activation and recruitment of motor units in addition to the change in neural drive.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the increase in ⌬V ab /T E mainly occurred from a decrease in T E throughout application of the protocol, in addition to a higher amount of volume displaced by the compartment. In contrast to diaphragm and expiratory muscles, the inspiratory muscles of the rib cage develop more passive tension for active force development when stretched beyond their optimal size, 40 and perhaps this is why a greater shortening velocity was seen in ⌬V rcp /T I in relation to the other indexes. In general, the increase in shortening velocity could be explained by the activation and recruitment of motor units in addition to the change in neural drive.…”
Section: Discussionmentioning
confidence: 99%
“…–2 to –7%) in FEV 1 , FVC, and increases (approx. 20%) in R5 were previously reported in healthy subjects following 30 min [11, 32] and 60 min [9, 10] of continuous HYP with similar or higher intensity, while no decline was reported after 30 min of HYP with unmeasured but likely lower ventilation [33]. …”
Section: Discussionmentioning
confidence: 75%
“…A potential cause of the changes in lung function observed after HYP might be HYP-induced respiratory muscle fatigue [9, 10, 32, 40, 41] since flow generation is effort dependent, at high lung volumes [42, 43] affecting PEF and to a lesser extent FEV 1 [44], and at very low lung volumes [42] potentially affecting FEF 25 − 75% and FVC. Although asthmatics showed reduced respiratory muscle strength, possibly rendering them more prone to the development of respiratory muscle fatigue, and although FEV 1 and PEF were indeed reduced early during HYP 1 – consistent with early development of fatigue [40] – respiratory muscle fatigue as a cause of changes in lung function seems unlikely since changes resolved already during the course of HYP 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter study showed that the end-inspiratory lung volume (EIV) increase in V CW was mainly achieved by increasing endinspiratory volumes of the RCp and RCa, reflecting the inspiratory RC muscle contribution to recruit the inspiratory reserve volume. Findings reported by Illi et al [75] likely indicate that all inspiratory muscles fatigued simultaneously rather than in succession and that inspiratory RC muscles did not take over diaphragmatic work in the course of prolonged normocapnic hyperpnoea.…”
Section: Breathing Evaluation Of Healthy Subjectsmentioning
confidence: 85%